Fairness and efficiency in resource allocation - Li, Zihao (Nanyang Technological University, 2025)
Fairness and efficiency are two fundamental topics in resource allocation. In resource allocation problems, we need to allocate a set of items to a set of agents. From an efficiency perspective, our goal is to maximize the total reward of the allocation. From the perspective of fairness, we want to ensure that every agent feels the allocation is fair. This thesis aims to identify required allocations from these different perspectives. We present our findings in three parts: (i) efficiency in online resource allocation, (ii) fairness in offline resource allocation, and (iii) fairness and efficiency in offline resource allocation.